Genomic Characterization and Functional Evaluation of Eurotium cristatum EC-520: Impacts on Colon Barrier Integrity, Gut Microbiota, and Metabolite Profile in Rats - Huini Wu; Xiuping Wang; Xiangrui Kong; Ruiyang Shan; Song Peng; Mengshi Zhao; Changsong Chen; Wenquan Yu; Zhaolong Li (Foods)
Eurotium cristatum (EC), the dominant fungus in Fuzhuan brick tea, has significant applications in food fermentation and pharmaceutical industries, exhibiting probiotic properties, but further investigation of its intestinal benefits is required. This study characterized the EC-520 strain through whole genome sequencing and evaluated its effects on rat colons using histomorphology, 16S rRNA sequencing, and untargeted metabolomics. The genomic analysis revealed that EC-520 possessed a 28.37 Mb genome distantly related to Aspergillus flavus. The 16S results demonstrated that EC-520 significantly increased the abundance of Bacteroidota (p < 0.05) while decreasing the Proteobacteria and Firmicutes/Bacteroidota ratio (the F/B ratio); at the genus level, it elevated Muribaculaceae and Clostridia_UCG-014 while reducing harmful bacteria. The metabolomic results showed that EC-520 also significantly altered tryptamine, caproic acid, isocaproic acid, and erucic acid (p < 0.05). Additionally, the Spearman’s correlation analysis revealed that Muribaculaceae_unclassified and Clostridia_UCG-014_unclassified were significantly positively correlated with tryptamine, caproic acid, isocaproic acid, and erucic acid. Therefore, this study suggested that EC-520 enhanced the colon barrier and increased the abundance of Muribaculaceae_unclassified and Clostridia_UCG-014_unclassified, thus promoting the secretion of tryptamine and affecting the release of 5-hydroxytryptamine (5-HT). It also promoted the secretion of certain fatty acids, enhancing the balance of the colonic microbiota. This study provides a new view for a comprehensive understanding of EC’s regulatory role in the colon.